The Impact of Foundation Medicine Testing on Cancer Patients: A Single Academic Centre Experience - Karol, Dalia; McKinnon, Mathieu; Mukhtar, Lenah; Awan, Arif; Lo, Bryan; Wheatley-Price, Paul (Frontiers in Oncology, 2021)
Background: The use of Next-Generation Sequencing (NGS) has recently allowed significant improvements in cancer treatment. Foundation Medicine (FM) ® provides a genomic profiling test based on NGS for a variety of cancers. However, it is unclear if the Foundation Medicine test would result in a better outcome than the standard on-site molecular testing. In this retrospective chart review, we identified the FM cases from an academic Canadian hospital and determined whether these test results improved treatment options for those patients. Materials and Methods: A retrospective analysis was performed on patients with solid tumors who had FM testing between May 1st, 2014 and May 1st, 2018. Clinical factors and outcomes were measured using descriptive statistics using Microsoft Excel ® Software. Results: Out of 66 FM tests, 8 patients (= 12%) had a direct change in therapy based on the FM rests. 285 oncogenic mutations were identified (median 1, range 0-31); where TP53 (n=31, 10.9%), CDKN2A (n=19, 6.7%), KRAS (n=16, 5.6%) and APC (n=9, 3.2%) were the most common FM mutations identified. Conclusion: A small proportion of FM reports identified actionable mutations and led to direct treatment change. FM testing is expensive and a few of the identified mutations are now part of routine on-site testing. NGS testing is likely to become more widespread, but this research suggests that its true clinical impact may be restricted to a minority of patients.